Analysis Low Proficiency Level Students’ Anxiety During Speaking English - Salsa bila (Nalar Global, 2021)
Anxiety is the state of feeling nervous or worried about something bad is going to happen. Some people in general situation will feel this feeling when they have no prepared or lack confidence. Example when a foreign language learner trying to speaking in English. Speaking skills are the skills that give someone the ability to communicate effectively. They give people the ability to convey information verbally and in a way that the listener can understand. This article aims to define the students' anxiety while speaking in English and its effect on students’ speaking skills so that they have a low proficiency level speaking English. This article also provides the factors that cause low proficiency level students’ anxiety during speaking English. This article uses some references such as journals, books, and other articles to get the data.